Delayed asymptomatic blunt traumatic diaphragmatic hernia: an unusual case report - Cylla Revata; Mulia Rahmansyah (Universa Medicina, 2022)
IntroductionTraumatic diaphragmatic hernia (TDH) is uncommon, being encountered in around 0.8%-8% of patients with blunt abdominal trauma. Severe comorbidities such as fractures and thoraco-abdominal or head injuries that accompany TDH, are responsible for poor prognosis and often mask diaphragmatic injury itself. Objective of this case report was to highlight rare blunt TDH case to avoid missed diagnosis leading to complications. Case descriptionSixty seven-year old man presenting with right chest pain without difficulty of breathing after falling from stairs 1 hour before hospital admission. On clinical examination, vitals were stable, but with decreased breath sounds on right lower side of chest. Patient had history of trauma from being crushed by elevator 40 years ago without any proven diaphragmatic injury. Initial erect chest X-ray findings were inhomogeneous opacity shadow on lower right hemithorax suspected to be diaphragmatic hernia and 7th right rib fracture with pleural effusion. Thorax CT scan showed herniated right lobe of liver, gall bladder, and mesenteric fat on right hemithorax causing displacement of mediastinal structures. Patient was diagnosed with delayed TDH and hemothorax caused by newly fractured rib. Patient was referred to a better-equipped facility due to the limited surgical facilities in referring hospital. ConclusionDelayed TDHs are not common, but can lead to serious consequences. Blunt TDH occurs more often on left than on right side, in ratio of approximately 3:1. Traumatic diaphragmatic hernia is sometimes diagnosed many years after traumatic event due to latent phase of disease possibly ranging from days to years.